SOSIALISASI PEMANFAATAN MINYAK JELANTAH MENJADI LILIN - Manzilatussyifa, Manzilatussyifa; Apriani, Nadila; Rezkiani, Putri; Pauziah, Rahmi Siti; Pura, Reza Wildan Endang; Syahidah, Syifa Qolbi; Nurkhofifah, Wifa; Mulyani, Eva (LPPM Universitas Bina Bangsa, 2024)
The excessive use of cooking oil and the disposal of used cooking oil waste can have negative impacts on health and the environment. This community service activity aims to raise awareness among the PKK (Family Empowerment and Welfare) women in Dusun Gunung Roay 2 about the management of used cooking oil by processing it into candles. The methods used include socialization through seminars and technical training on candle-making from used cooking oil. Participants are taught practical steps for processing and receive direct guidance during the practice sessions. Observations are conducted to monitor participation and the skills of the socialization participants. The results show an increase in awareness and understanding among participants regarding the importance of maintaining health and environmentally friendly waste management efforts. This activity is expected to enhance active community participation in preserving the environment and health through the management of household waste. This topic was chosen due to the significance of household waste management, particularly used cooking oil, in safeguarding health and the environment, as well as the potential for productive utilization of this waste.